Rhinoscleroma: a case report - Karpińska-Kaczmarczyk, Katarzyna; Chosia, Maria; Woyke, Stanisław (Polish Journal of Pathology, 2010)
Rhinoscleroma is a chronic inflammatory disease in which granulation tissue with a typical cell content is found. The paper presents the case of a 77-year-old woman with clinically diagnosed nodule in the nasal cavity. The histopathological examination revealed granulation tissue with plasma cells and Mikulicz’s cells. The clinical and morphological picture of the case in question is a rare opportunity to bring to mind a disease that used to be common in Poland and which clinically can imitate malignant tumour.